ACCOUNTING FACTORS AFFECTING THE DECISION TO INVEST IN SHARES OF JOINT STOCK COMPANIES IN IRAQ - Halah Nomas Othman (Scholars Digest Publishing, 2023)
The aim of this research is to identify the accounting factors affecting the decision to invest in shares of joint-stock companies in Iraq and what is the degree of impact of those factors. To achieve the objectives of the study, the analytical descriptive approach was used, and a questionnaire was designed and distributed to a sample of investors in the Iraq Stock Exchange. As they numbered (38) investors, the data of the study were analyzed by the statistical package program (SPSS). The research concluded a set of conclusions, the most important of which are: that one of the most important accounting factors is the analysis of the annual and interim financial reports of the company, reviewing the auditor's report and obtaining the share of the realized profits, as well as the presence of a significant effect of the accounting factors on the investment decision in the shares of joint stock companies. The research concluded with a set of recommendations, the most important of which was to work on issuing laws, regulations and publications that oblige the establishment to apply accounting standards that contribute to the rationalization of investment decisions.
Keywords: accounting factors, investment decision, shareholding companies in Iraq, investor profitability, stock market, investor decisions.